2010
DOI: 10.1111/j.1365-2966.2009.16043.x
|View full text |Cite
|
Sign up to set email alerts
|

The JCMT Nearby Galaxies Legacy Survey - III. Comparisons of cold dust, polycyclic aromatic hydrocarbons, molecular gas and atomic gas in NGC 2403

Abstract: We used Spitzer Space Telescope 3.6, 8.0, 70 and 160 μm data, James Clerk Maxwell Telescope HARP‐B CO J= (3–2) data, National Radio Astronomy Observatory 12 m telescope CO J= (1–0) data and Very Large Array H i data to investigate the relations among polycyclic aromatic hydrocarbons (PAHs), cold (∼20 K) dust, molecular gas and atomic gas within NGC 2403, an SABcd galaxy at a distance of 3.13 Mpc. The dust surface density is mainly a function of the total (atomic and molecular) gas surface density and galactoce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 105 publications
(203 reference statements)
6
32
3
Order By: Relevance
“…Bendo et al (2010) have used Spitzer imaging of NGC 2403 at 70 μm and 160 μm to map the dust column density via its thermal emission. They also used the far-IR images in conjunction with H i observations to map the gas/dust ratio.…”
Section: An Interstellar Echomentioning
confidence: 99%
“…Bendo et al (2010) have used Spitzer imaging of NGC 2403 at 70 μm and 160 μm to map the dust column density via its thermal emission. They also used the far-IR images in conjunction with H i observations to map the gas/dust ratio.…”
Section: An Interstellar Echomentioning
confidence: 99%
“…The detailed study of these resolved galaxies will not only act as a benchmark for studies of more distant galaxies, but will also bridge the gap between surveys of distant objects and the extensive Galactic surveys which have superior physical resolution but by their nature are limited to observations of one galaxy. Recent results from the VNGS include determining the nature of dust heating in M81 (Bendo et al 2010), attempting to separate Galactic cirrus emission from extragalactic dust emission in M81 (Davies et al 2010) and studying the dust distribution and heating mechanisms in and around the starburst galaxy, M82 (Panuzzo et al 2010;Roussel et al 2010). While this paper concentrates on the external dust around Cen A, a detailed analysis of the dust within Cen A will be discussed by Parkin et al (2011).…”
Section: Very Nearby Galaxy Surveymentioning
confidence: 99%
“…The data were processed using the MIPS Data Analysis Tools (Gordon et al 2005) along with additional processing steps decribed by Bendo et al (2010) and Bendo et al (in preparation). The additional processing steps include an additional flat-fielding step for the 24-μm data; the removal of latent images from the 24-μm data; background subtraction in all three wave bands (including zodiacal light subtraction in the 24-μm band and short term drift removal in the 70-and 160-μm bands); and a non-linearity correction applied to the 70-μm data.…”
Section: Mid-and Far-infrared Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the properties of the 8 µm emission and of the CO emission presented in [4] showed that, on large scales, the emission of molecular gas is correlated with the emission of small dust grains, namely, polycyclic aromatic hydrocarbons (PAHs; in particular, their radial profiles have statistically equivalent scale lengths); however, this correlation weakens on smaller scales. Such relationships are interesting because they shed light on the origin of so-called "CO-dark" molecular gas, i.e., gas with a very low CO abundance, even though most of the hydrogen has already been converted into molecular form.…”
Section: Introductionmentioning
confidence: 99%